SAT0416 Ankylosing spondylitis disease activity score (ASDAS) is associated with nsaid use over time. (15th June 2017) - Carbo, MJ; Arends, S; Maas, F; Bouwer, E; Bos, R; Bootsma, H; Veer, E van der; Wink, F; Spoorenberg, A
Abstract : Background: Non-steroidal anti-inflammatory drugs (NSAIDs) are the cornerstone of conventional treatment in ankylosing spondylitis (AS). In case of insufficient response, tumor necrosis factor-alpha (TNF-α) inhibitors are available. Still little is known about concomitant NSAID use. Objectives: To investigate the longitudinal association between disease activity and NSAID use in established AS patients. Methods: The present analysis is part of the GLAS cohort, an ongoing longitudinal observational axial spondyloarthritis (SpA) cohort study in daily clinical practice. During 52 weeks of follow-up, NSAID use was recorded prospectively. The ASAS-NSAID index was calculated using the dosage and frequency assessed retrospectively from clinical records. Disease activity was assessed using ASDAS, BASDAI, and serum CRP levels. Generalized estimating equations (GEE) was used to evaluate NSAID use in relation to assessments of disease activity over time. NSAID use was analyzed using 4 parameters: NSAID use (yes/no), ASAS-NSAID index, low on demand use (index ≥10 versus <10), and high use (index ≥90 versus <90). Analyses were stratified for treatment regimen: patients starting TNF-α inhibitors and patients on conventional treatment. Results: Of the 393 included AS patients, 67% were male, mean age was 44±13 years, median symptom duration 15 years (IQR 8–24), and 79% were HLA-B27 positive. In total, 254 (66%) patients started TNF-α inhibitors and 139 (34%) patients received conventional treatment. Patient characteristics were comparable between both groups, except higher disease activity, more often peripheral arthritis, and worse physical functioning in patients starting TNF-α inhibitors. NSAID use and disease activity reduced significantly after starting TNF-α inhibitors and remained low and stable during follow-up. In the conventional treatment group, disease activity was low and NSAID remained stable at all visits. GEE analysis over time showed that NSAID use was significantly associated with disease activity (Table 1 ). In the TNF-α inhibitor group, a significant association of all NSAID parameters with ASDAS was found: NSAID use yes vs. no, ASAS-NSAID index, index ≥10 vs. <10, and index ≥90 vs. <90. Comparable results were found for BASDAI and CRP. The association between NSAID use and ASDAS remained significant in the 217 patients who used TNF-α inhibitors more than 80% of the follow-up time and when analyzing only 12 to 52 weeks of follow-up to exclude the initial effect of TNF-α inhibitors, although the regression coefficients were lower in these last analyses. In the conventional treatment group, a significant but less prominent association of NSAID parameters with ASDAS was found: NSAID use yes vs. no, index ≥10 vs. <10, and index ≥90 vs. <90. BASDAI was only significantly associated with on demand NSAID use. For CRP, no significant associations with NSAID use were found. Conclusions: In this observational cohort of established AS patients, NSAID use over time was significantly associated with ASDAS, which was most pronounced for patients treated with TNF-α inhibitors. Acknowledgements: The GLAS cohort was supported by an unrestricted grant from Pfizer. Pfizer had no role in the design, conduct, interpretation, or publication of this study. Disclosure of Interest: None declared